2023
DOI: 10.1051/e3sconf/202337605031
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a risk-based OHS management system at IMC mining company

Abstract: IMC mining company produces gold and silver. In mining operations that are carried out every day in the workplace, there must be dangers and risks. All these hazards are more related to the transport systems and transport used in the mining process. International mining company (IMC) underground mines definitely have operations division jobs with a high level of risk against work accidents, for example, maintenance of transport installations and the systems. Therefore, it is important to identify hazards, risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Any failures in the process of assessing the risks of OHS add to the challenges of implementing an OHSMS [13,19]. Studies have shown that construction accidents are mostly attributed to workers' mistakes and flaws in the risk management plan [23]. Most incidents or accidents occur because of a lack of recognition towards the hazards and risks related to work or activities in the workplace [23].…”
Section: Integrating Risk Management Into Ohsmssmentioning
confidence: 99%
See 1 more Smart Citation
“…Any failures in the process of assessing the risks of OHS add to the challenges of implementing an OHSMS [13,19]. Studies have shown that construction accidents are mostly attributed to workers' mistakes and flaws in the risk management plan [23]. Most incidents or accidents occur because of a lack of recognition towards the hazards and risks related to work or activities in the workplace [23].…”
Section: Integrating Risk Management Into Ohsmssmentioning
confidence: 99%
“…Studies have shown that construction accidents are mostly attributed to workers' mistakes and flaws in the risk management plan [23]. Most incidents or accidents occur because of a lack of recognition towards the hazards and risks related to work or activities in the workplace [23]. Managing risks in the construction industry is necessary to methodically assess general risk management factors for safeguarding different project participants [22].…”
Section: Integrating Risk Management Into Ohsmssmentioning
confidence: 99%